(untitled) (Research, Society and Development, 2021)
Biofouling is one of the main problems that affect oyster crops. In this study, it was tested the hypothesis that the richness and abundance of macrobentos that make up biofouling are associated with the surface area of the oyster Crassostrea tulipa cultivated in the Urindeua River, Pará. For this, nine collections were carried out between May 2016 and April 2017, showing 30 oysters/month in an oyster crop located on the Amazon coast. First, biofouling of the oyster surface was removed, and the classification, quantification and taxonomic identification of the organisms were subsequently carried out. To test possible differences between oysters of different sizes in relation to the parameters richness and abundance of biofouling, a ANOVA one-way was applied, used a Tukey’s post hoc test. The results of this study confirm the hypothesis that the richness of biofouling is associated with the oyster surface, indicating that larger oysters have a higher number of species when compared to smaller ones. However, it refuted the hypothesis when abundance was related.